Influence of heat stress on the expression patterns of different cytokine genes in Malabari goats - Rasha Mol, V P (Academy of Climate Change Education and Research, 2018)
Heat stress acts as detrimental factor for immune functions in farm animals. The impact of heat stress in particular on immune system related gene expression has not been elucidated in farm animals. Therefore, research efforts pertaining to quantifying the impact of heat stress on immune system related gene expression are crucial for development of superior thermo-tolerant breeds with potent immune competency. Hence, a study was conducted with the primary objective to determine the impact of heat stress on different mesenteric lymph node (MLN) associated cytokine gene expression patterns and histopathological changes in heat stressed goat. To satisfy this objective, a study was conducted in twelve 10 months to one year old Malabari breed goats for 45 days duration. The goats were randomly allocated into two groups: C (n=6; Control) and HS (n=6; Heat stress). Goats were stall-fed with a diet composed of 60% roughage and 40% concentrate. All animals had access to ad-libitum feed and water and they were fed and watered individually. The C goats were placed in the shaded pens while HS goats were exposed to heat stress in outside environment between 10.00 h to 16.00 h. The animals were slaughtered at the end of the study and their representative MLN samples were collected for assessing the different cytokine gene expression and histopathological changes. The expression patterns of interleukin-I and IL-IO were comparable between C and HS groups. However, the expression patterns of IL-18, tumor necrosis factor-a (TNF-a), interferon-f (IFN-P) and IFN-y were significantly (P<0.05) down regulated in HS group as compared to the C group animals. In addition, a strong negative correlation (P<0.01) was also established for THI with IL-18, TNF-a, and IFN-y gene expression in the study. The histopathological changes of MLNs showed paucity of lymphocyte distribution in the follicular areas as wells as decreased density of lymphocytes in the germinal centres of HS group (P<0.05) compared to C group. The findings from this study clearly indicated the compromised immune functions during heat stress exposure in Malabari goats.This is evident from the down regulation of most of the cytokine gene expressions as well as through the histopathological changes observed in MLN. The study also identified IL-18, TNF-a, and IFN-y genes to be the ideal immunological markers for quantifying the heat stress mediated immune response in goats. These candidate genes which form the molecular basis for controlling the immune system in Malabari goats during heat stress may be used as immunological markers for developing appropriate breeding program to establish a goat breed with superior immune competency.